2001
DOI: 10.1161/hc4401.098516
|View full text |Cite
|
Sign up to set email alerts
|

Intracoronary β-Radiation Exacerbates Long-Term Neointima Formation in Balloon-Injured Pig Coronary Arteries

Abstract: Background Long-term biological effects of ionizing radiation on coronary arteries remain poorly defined. We examined late arterial responses 6 months after balloon angioplasty and β-radiation in normal pig coronary arteries. Methods and Results Coronary arteries of 25 adult pigs were randomized to receive 20 Gy (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0
1

Year Published

2002
2002
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 32 publications
2
12
0
1
Order By: Relevance
“…In contrast, with vascular brachytherapy, only 33% of the intimal surface of 6-Ci ␤-emitting stents is endothelialized at 3 months, and the degree of delayed healing with vascular radiation therapy is far greater (increased intimal fibrin deposition and inflammation) than that observed with everolimus in the present study. 17,25 To our knowledge, no other studies of drug-eluting stents have assessed the extent of stent endothelial coverage at 28 days by scanning electron microscopy. Even with a semiquantitative light microscopic method, the stent endothelialization score of porcine coronary arteries with sirolimuseluting stents was 2.9, corresponding to Ͻ75% stent surface endothelial coverage.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, with vascular brachytherapy, only 33% of the intimal surface of 6-Ci ␤-emitting stents is endothelialized at 3 months, and the degree of delayed healing with vascular radiation therapy is far greater (increased intimal fibrin deposition and inflammation) than that observed with everolimus in the present study. 17,25 To our knowledge, no other studies of drug-eluting stents have assessed the extent of stent endothelial coverage at 28 days by scanning electron microscopy. Even with a semiquantitative light microscopic method, the stent endothelialization score of porcine coronary arteries with sirolimuseluting stents was 2.9, corresponding to Ͻ75% stent surface endothelial coverage.…”
Section: Discussionmentioning
confidence: 99%
“…These findings corroborate previous animal studies in which the antiproliferative effect of irradiation was no longer observed at 6 months with 15 Gy. 19,20 Thus, higher doses may be necessary to prolong the effectiveness of irradiation over time. Interestingly, the present study did not find differences in the absolute and the rate of reendothelialization of the examined doses to support a longer duration of antiplatelet therapy for 30 Gy over 15 Gy.…”
Section: Cheneau Et Al Time Course Of Stent Endothelializationmentioning
confidence: 99%
“…The 2 most important issues have been late thrombosis and delayed restenosis, which may be caused by delayed endothelial regeneration and aggravated inflammatory cell infiltration. [3][4][5] Presently, no adjuvant therapy is available for modulating the disturbed healing process after intravascular radiation therapy.…”
mentioning
confidence: 99%